„Polityka solna” Rzeczpospolitej szlacheckiej u progu rozbiorów - Kowalczyk, Rafał Wiktor (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
Article relates to question of “salt policy” of The Republic of Noble; attempt to reform of the system; the government and the ruler want of increasing budget income. Attempted reforms have been analyzed and reasons for their failure highlighted. Weakness of Republic and its lasting in the shackles of feudal prerogatives did not permit such success of “salt policy”, as in neighboring countries of central-east Europe: Russia, Prussia and Austria. Due to this reason “Polish” salt was eliminated from the foreign markets while the king resigned from expansion on home market – Prussian territory and Grand Duchy of Lithuania. The Noble Republic for several hundred years could not create a significant instrument of income from “salt policy”; Austria – country of strong central structures, which in 1772 took over “Polish” salt mines – both Krakows and Russians – achieved this goal in several months.